Family property among the Yorubas - Coker, G. B. A. (London, Sweet and Maxwell; Lagos, African Universities P., 1966)
The book discusses the Yoruba inheritances and succession as it concerns customary law. Yoruba customary law, to a member of the legal profession, consists of those legal rules currently accepted by the High Court; to me-and of course to most Yoruba-it consists of the rules applied in the customary courts. The High Court has taken a long time to formulate a satisfactory concept of family property. Most of the cases reported refer to Lagos in which town there are no customary courts; the judges do not have the benefit of a lower court judgment based on customary law alone. Lagos chiefs are called to give evidence of Yoruba law but these men have not the experience of customary court judges.
Includes index
Bibliography: p. 389-391.
usc 23/01/2019
Loans
Keywords: Property (Yoruba law); Inheritance and succession (Yoruba law); Property; Inheritance and succession; Customary law; Land tenure (Primitive law); Nigeria